Behavior of fiber reinforced concrete members under sustained axial/flexural load. (6th November 2019) - Watts, Murray J.; Amin, Ali; Gilbert, Raymond Ian; Kaufmann, Walter
Abstract: The inclusion of steel or polypropylene fibers in the concrete mix can substantially improve the serviceability characteristics of reinforced concrete members. For fiber reinforced concrete (FRC) members, the fibers enhance the postcracking stiffness, thereby reducing the short‐term and long‐term deflections, and very significantly reducing the width of cracks and the spacing between them. Relatively little experimental and analytical research has been undertaken on the effects of creep and shrinkage on the long‐term performance of FRC structural members after cracking. Failure to account for creep and shrinkage of the concrete and creep of the fibers can lead to a serious under‐estimation of the extent and severity of cracking, as well as long‐term curvatures and deformations. This paper describes a method of analysis and the material modeling required to determine the time‐dependent behavior of cracked, steel or macro‐synthetic FRC members containing conventional bar reinforcement and subjected to a sustained bending moment and/or axial force. The model is versatile in that it can handle a range of inputs (fiber type, specimen geometry, loading conditions, etc.) and is simple enough for routine use. The model is validated against available test data and is shown to produce satisfactory correlations.